Deficit in financing investment in electric power in this decade in Latin America: possible solutions - Kuczynski, Pedro-Pablo (OLADE QuitoEC)
Discusses from a financial engineering standpoint, what types of mechanisms could be developed, to cover the obvious lack of financing to be faced by electric power investment programs in most of the countries of Latin America in the next few years.